A Few Words about the Hybrid Nature of Mawlid’s Text of the 18th Century - Kozhinowa, Alla (Lietuvos istorijos studijos, 2023)
The present article focuses on the text created by Belarusian–Polish–Lithuanian Tatars that admires the birth of the Prophet Muhammad with the ap- propriate title “Mawlid” (Birth). The time of text creation is unknown. Although, the last rewriting of the manuscript is most likely to have taken place no earlier than the second half of the 18th century, that is, according to some researchers, when the Polish language prevailed in texts written by the Tatars who lived on the territory of the Grand Duchy of Lithuania. The language of the text under consideration can be described as hybrid. Hybrid texts were based on a native speaker’s linguistic capabilities with an orientation to some book that served an example. On the one hand, the linguistic structure of such a text reflected the idiolect of its creator, and, on the other hand, it included the elements of the book example the creator was guided by. The objective of the article is to study the lexi- cal structure of the text in question which is a mixture of lexemes belonging to different languages. There are a number of Arabic and Turkish words in the text. Regarding Slavonic words, it is difficult to determine their origin accurately due to genetic links of the languages. Definitely, there have been attested lexemes be- longing to Common Slavic, along with Church Slavonic and East Slavonic words of Polish origin. In conclusion, it is assumed that norms pertaining to the Polish language became weaker gradually. This statement can be supported by the fact that “Mawlid” (Birth) was created no earlier than the 18th century, when the ter- ritories bordering the Russian Empire alongside the territories which had entered the Russian Empire after partitioning the Polish–Lithuanian Commonwealth were greatly influenced by the East Slavonic dialects as well as standards in writing. The fact that there is a mixture of not only phonetic and morphological but also lexical elements in the text does not seem to suggest that such a process took place only as a result of repeated text rewriting. There also may be a case typical of undifferentiated multilingualism when a speaker does not separate the system of languages and uses the first option that comes to mind without thinking about its linguistic affiliation.
Keywords: Belarusian–Lithuanian–Polish Tatars; hybrid texts; manuscript in Arabic script; Mawlid; Slavic languages